Between Home and Dormitory: Navigating Student Behavior and Parental Satisfaction in Urban Islamic Hybrid Boarding Schools - Zamal, Syahrul; Cholily, Yus Mochamad; Baiduri; Utomo, Dwi Priyo (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
Urban families in metropolitan contexts increasingly face challenges related to limited parental supervision, time constraints, children's social environments, and the need for schools that can provide both academic learning and character formation. In response to these conditions, Islamic hybrid boarding schools have emerged as an educational innovation that integrates regular schooling, dormitory-based supervision, Islamic character mentoring, and more flexible family involvement. This study examines student behavior in an Islamic hybrid boarding school environment and analyzes its relationship with parental satisfaction. A mixed-methods sequential explanatory design was employed, involving 12 parents of students at SMP Muhammadiyah 8 Jakarta selected through purposive sampling. Quantitative data were collected using a structured questionnaire measuring student behavior and parental satisfaction on a four-point Likert scale, while qualitative data were obtained through semi-structured interviews, observations, and field notes to enrich the interpretation of statistical findings. Data were analyzed using validity, reliability, normality, descriptive statistics, and simple linear regression tests (SPSS version 30). The results demonstrate that the instrument was highly reliable (Cronbach's α = 0.903), and that student behavior jointly explained 91.7% of the variance in parental satisfaction (F = 29.374, p < 0.001). Academic engagement, socio-emotional behavior, and personal behavior each contributed strongly to parental satisfaction, with individual R² values of 0.887, 0.878, and 0.873, respectively. These findings indicate that parents evaluate Islamic hybrid boarding school quality primarily through visible behavioral transformation in their children, including academic discipline, independence, responsibility, and religiosity. The study implies that boarding-based Islamic schools should strengthen systematic behavioral monitoring and parent–school communication as core components of educational quality assurance and institutional sustainability.